Time for learning : top 10 reasons why flipping the classroom can change education - Fulton, Kathleen (Corwin, a SAGE Company, 2014)
The guide school leaders need to reap the rewards of education's most exciting new trendFlipping classrooms-using class time for hands-on learning and ""off loading"" the lecture portion of lessons as homework-is taking schools by storm. This book makes the case to educational leaders for the benefits of flipping. Backed by powerful data and anecdotes, topics include: Data on positive student outcomes in terms of achievement and motivation How flipping gives teachers more time to work with students one-on-one and encourage peer learning How flipping engages students in 21st centu